1999
DOI: 10.1063/1.125245
|View full text |Cite
|
Sign up to set email alerts
|

Polymerized carbon nanobells and their field-emission properties

Abstract: Aligned nitrogen-containing carbon nanofibers consisting of polymerized “nanobells” have been grown on a large scale using microwave plasma-assisted chemical-vapor deposition with a mixture of methane and nitrogen. A greater part of the fiber surface consists of open ends of the graphitic sheets. A side-emission mechanism is proposed. A low-threshold field of 1.0 V/μm and a high-emission current density of 200 mA/cm2 for an applied field of 5–6 V/μm were achieved, implying that the materials have a high potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(85 citation statements)
references
References 18 publications
3
80
2
Order By: Relevance
“…These proposals, based on a conception that the growth of a tube is catalyzed by single catalyst particle, can explain the formation of the type I bamboo-shape carbon nanotubes because, as mentioned above, only one catalyst particle exists at the end of this type of tubes. It should be pointed out that some authors found that the presence of nitrogen-containing gases (N 2 or NH 3 ) promotes the formation of bamboo-shape tubes [11], [12], [13], [22], [23] and [24], but our experimental results show that N 2 does not play a key role in their formation, at least in our reaction system. Although a large amount of N 2 is produced from the decomposition of PA and involved during the tube growth, normal tubes can be obtained under a similar N 2 -rich environment by controlling other experimental parameters.…”
Section: The Growth Of Bamboo-shape Cntscontrasting
confidence: 76%
See 2 more Smart Citations
“…These proposals, based on a conception that the growth of a tube is catalyzed by single catalyst particle, can explain the formation of the type I bamboo-shape carbon nanotubes because, as mentioned above, only one catalyst particle exists at the end of this type of tubes. It should be pointed out that some authors found that the presence of nitrogen-containing gases (N 2 or NH 3 ) promotes the formation of bamboo-shape tubes [11], [12], [13], [22], [23] and [24], but our experimental results show that N 2 does not play a key role in their formation, at least in our reaction system. Although a large amount of N 2 is produced from the decomposition of PA and involved during the tube growth, normal tubes can be obtained under a similar N 2 -rich environment by controlling other experimental parameters.…”
Section: The Growth Of Bamboo-shape Cntscontrasting
confidence: 76%
“…The wall thickness is also not constant along the compartment, declining smoothly from the closed dome to the open side. Such a structure is somewhat similar to the CN x "nanobell"-gathered fibres produced by plasma-enhanced CVD technique [11] and [12], although the individual nanobell is much shorter than the individual compartment of the type II tubes. Fig.…”
Section: Morphologies and Structures Of Bamboo-shape Cntsmentioning
confidence: 58%
See 1 more Smart Citation
“…4,5,7 Distinctively, a great part of the bamboo-like nano-structures consists of open ends of relatively short CNTs. 18,19,20 Individual short CNTs are weakly stacked one on top of the other to create a long nano-fiber. The observed bamboo-like structure along the nano-fiber length can be attributed to the integration of nitrogen into the graphitic structure, altering the nanotube surface from straight cylinder geometry.…”
Section: Optimized Carbon Nanotube Structuresmentioning
confidence: 99%
“…Nitrogendoped carbon nanotubes render them n-type material regardless of tube chirality 39 , and nitrogen in doped carbon nanotubes acts as a donor. In particular, nitrogen-doped carbon nanotubes are effective field emitters [40][41][42][43] . CNx nanotubes have been demonstrated to show lower turn-on and higher current density than undoped carbon nanotubes 42 .…”
Section: Structural Properties and Enthalpy Of Formationmentioning
confidence: 99%